CHEAP SYARIAH QURBAN INVESTMENT (CSQI) PROGRAM: DETERMINING FACTORS OF POTENTIAL PARTICIPANTS DECISION MAKING - Novra, Ardi; Adriani; Oktavia, Ade; Depison (International Journal of Research -GRANTHAALAYAH, 2021)
The evaluation of community service activities (CSA) for the regional superior product development program (RSDP) is to analyze qurban behavior and the determining factors that influence program decisions. A survey of 87 participants in the CSQI program surgery was conducted online from several groups, both experienced and inexperienced as committee members and qurban worship participants. The results of the evaluation of potential candidates for qurban participants show that generally the sources of information coming from academics, practitioners and the bureaucracy are interested (56.17%) to participate in the CSQM program, while the parties have not decided (42.52%) and are not interested at all (2,29%). A person's experience both in participating in the management of qurban activities and as a participant does not significantly influence their decision to join the CSQI program. The decision to participate in the CSQI program is determined by the payment system, the information they receive and the level of their readiness to face qurban activities in the next period. Based on the results of the evaluation, it can be concluded that the promotion and marketing policies of the CSQI program need to be improved or modified in order to provide clear information and provide an alternative arisan (installment) repayment system and so that the effectiveness is focused on the target market segment in the form of religious-related qurban management institutions, offices and neighborhood association.